Cotton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Watson Mwale of Zambia?s Cotton Development Trust explains some recent developments in weed control for cotton, including the weed wiper, and discusses weed control in conservation farming systems.